2019
DOI: 10.3390/s19163473
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Odor Intensity of Binary Gas Mixtures Using Perceptual Models and an Electronic Nose Combined with Fuzzy Logic

Abstract: Measurement and monitoring of air quality in terms of odor nuisance is an important problem. From a practical point of view, it would be most valuable to directly link the odor intensity with the results of analytical air monitoring. Such a solution is offered by electronic noses, which thanks to the possibility of holistic analysis of the gas sample, allow estimation of the odor intensity of the gas mixture. The biggest problem is the occurrence of odor interactions between the mixture components. For this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Sensors 2020, 20, x FOR PEER REVIEW 3 of 12 procedure and environmental requirements were described in these references. In this study, the collected dataset contains 31 samples of binary mixture EA+BA, 21…”
Section: Support Vector Regression Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Sensors 2020, 20, x FOR PEER REVIEW 3 of 12 procedure and environmental requirements were described in these references. In this study, the collected dataset contains 31 samples of binary mixture EA+BA, 21…”
Section: Support Vector Regression Methodologymentioning
confidence: 99%
“…The influences of assessor quantity, age, gender, and testing environments could be avoided [36]. On the other hand, it has been reported that the e-nose can directly perform odor intensity evaluation [21,37]. However, it directly correlates the sensor signal and odor intensity, and does not fully consider the gas mixture's composition.…”
Section: Odor Intensity Predictive Performance Of the Svr Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting estimate from the vector model is a profile of OI values, which represent the combination and relative strengths of ODs imparted by the mixture. The odour vector model has been successfully applied to binary [ 26 29 ], ternary [ 30 ], quaternary [ 31 , 32 ], and quinary mixtures [ 24 ]. However, noting that natural product odours—such as those from flowers or fruits—are mixtures of larger numbers of volatile compounds, there is an interest in expanding this modelling process to assess its utility within the context of representative profile complexity.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Szulczy ński et al proposed a fuzzy logic algorithm for the determination of the odor intensity of the binary mixtures of eight odorants: n-Hexane, cyclohexane, toluene, o-xylene, trimethylamine, triethylamine, α-pinene, and β-pinene. In this research, a prototype of an e-nose equipped with eight gas chemical sensors (one photoionization, two electrochemical, and five metal oxide semiconductor sensors) was used [26]. In 2021, Zhou et al evaluated the floral volatile profile of six Hedychium accessions using HS-SPME-GC-MS and e-nose technology.…”
Section: Introductionmentioning
confidence: 99%